Thinking with care in human–computer interaction. (April 2022) - Croon, Anna
In this article, human–computer interaction (HCI) is explored as a design-oriented practice nurturing the becoming of what is not-yet in future-oriented and speculative manners. Such approaches have evolved over time and now the field seems ready to take leaps targeting social and culturally infused contexts, such as those suggested by critical design, design things, adversarial design, making futures, pluriversal design and critical fabulations. It is in this respect that feminist theories, methods and imaginaries are rendered important. Feminist theory is in this article considered an important companion and part of the practical tool-kit necessary for generative, speculative and ethical approaches within the field of HCI. How to think with care is explored as a meta-design strategy directed and informed by feminist onto-epistemologies – a strategy intended to 'seed' speculative and social justice-oriented design endeavours through generative figurations and critical dilemmas to foster abilities and sensibilities for dealing with difference differently. What is advanced is the need for meta-design space in HCI, in this article referred to as a contact zone, a feminist figuration with the intention to open up for design explorations with ethical imperatives. Four other interrelated feminist figurations are also loosely explored in order to frame how thinking with care in HCI could be advanced further, i.e. diffractive thinking, intra-activism, becoming-with and response-ability. By considering serious feminist accounts of situated knowledges and touching visions, it is argued that feminist thinking is well on its way to offering real alternatives of great importance for HCI.